Failure Analysis of Axial Compressor Rotor Blade on Alshtom Gas Turbine with Capacity 20 MW at PLTGU - Maulana Nasution, Ahmad Rizki; Hestiawan, Hendri; Suryono, Ahmad Fauzan (UNIB Press, 2021)
This was the work in one of the Gas-Steam Power Plant (PLTGU) in the Southern Sumatra. The compressors on the Alsthom gas turbine suffered damage to the rotor blade section causing it to stop operations. In this study discussed the analysis of the cause of damage to the axial compressor rotor blade with the aim of knowing the causative factors of damage, the mechanism of damage, the shape of the microstructure and the size of the grain. Observations are made by direct macro observations. After making observations, it continues with the analysis of observations. From the results of the analysis, it was concluded that the damage occurred was influenced by several factors, namely corrosion, service life and environmental conditions. If the damage is compared to the size of the grain then the part that is a lot of damage has a larger grain size compared to the slightly damaged part.